(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates a low-cost post-production workflow and equipment chain that meets the financial constraints of the Sri Lankan film industry while maintaining industry standard visual quality. Post-production represents a significant amount of the production costs, often challenging independent and student filmmakers and other low-budget productions. The research identifies current post-production systems, evaluates their costs and standards, and explores human audio-visual perception to identify an affordable alternative. The proposed system incorporates a cost-effective combination of hardware and software optimized for efficient editing, color grading and creating DCI-recommended outputs. The workflow emphasizes streamlined processes including proxy-based offline editing, high-resolution confirmation, and final delivery to expected quality. The system and workflow were validated through the audio-visual content and a comparative analysis with two alternative versions. Focus group feedback assessed technical parameters such as brightness, contrast, color accuracy and emotional impact. The results show that the proposed workflow outperformed its counterparts by providing high-quality outputs within tangible constraints and budget constraints. The study concludes that the proposed workflow offers a practical solution for the film industry in Sri Lanka, balancing affordability with visual satisfaction. However, given the rapid evolution of post-production technology and artificial intelligence, continuous adaptability is essential to ensure long-term relevance and sustainability.